Antibiotic susceptibility pattern of Campylobacter sp. isolated from human stool samples including comparison of ellipsoid test and broth microdilution for meropenem - Fornefett, Juliane; Banerji, Sangeeta; Rimek, Dagmar (GMS Infectious Diseases)
Foodborne campylobacteriosis is the most common cause of bacterial gastroenteritis in Germany. Due to increasing antibiotic resistance in Campylobacter, data of isolates of human origin are published by the European Center for Disease Control and Prevention (ECDC)/European Food Safety Authority (EFSA). However, data on susceptibility to meropenem, an antibiotic of last resort, is not included. Therefore, the minimal inhibitory concentration (MIC) for meropenem was measured in 125 Campylobacter jejuni (Cj) and 57 Campylobacter coli (Cc) isolates isolated from human stool samples between 2020 and 2023, comparing ellipsoid test and broth microdilution. Additionally, we determined the susceptibility of 249 Cj and 84 Cc strains isolated between 2018 and 2023 to erythromycin, ciprofloxacin and oxytetracycline by disk diffusion according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST). For meropenem, the MIC results of 5% Campylobacter isolates were interpreted as resistant. Erythromycin resistance was found in none Cj versus 9 (11%) Cc isolates that were resistant to all three substances. Ciprofloxacin and oxytetracycline resistance were detected in 72 and 41% Cj, and 67 and 70% Cc isolates, respectively. Only 24% Cj and 13% Cc isolates were susceptible to all three substances. The dual resistance of ciprofloxacin and oxytetracycline was the most common resistance pattern, observed in 37% Cj and 38% Cc isolates, respectively. None of the isolates was resistant to all four tested substances. Our data underline the need for susceptibility testing of Campylobacter to alternatively used antimicrobial substances in clinical laboratories. The ellipsoid test provides a good alternative for meropenem MIC testing, although borderline isolates should be confirmed using microdilution.